Cardiac Autonomic Function in Patients With Ankylosing Spondylitis: A Case-Control Study. Issue 21 (May 2016) - Wei, Cheng-Yu; Kung, Woon-Man; Chou, Yi-Sheng; Wang, Yao-Chin; Tai, Hsu-Chih; Wei, James Cheng-Chung
Abstract : Abstract: Ankylosing spondylitis (AS) is a chronic inflammatory disease involing spine and enthesis. The primary aim of this study is to investigate the autonomic nervous system (ANS) function and the association between ANS and the functional status or disease activity in AS. The study included 42 AS patients, all fulfilling the modified New York criteria. All the patients are totally symptom free for ANS involvement and had normal neurological findings. These AS patients and 230 healthy volunteers receive analysis of 5 minutes heart rate variability (HRV) in lying posture. In addition, disease activity and functional status of these AS patients are assessed by Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), and Bath Ankylosing Spondylitis Global Score (BAS-G). Both groups were age and sex-matched. Although the HRV analysis indicates that the peaks of total power (TP, 0–0.5 Hz) and high-frequency power (HF, 0.15–0.40 Hz) are similar in both groups, the activities of low-frequency power (LF, 0.04–0.15 Hz), LF in normalized units (LF%), and the ratio of LF to HF (LF/HF) in AS patients are obviously lower than healthy controls. The erythrocyte sedimentation rate and C-reactive protein revealed negative relationship with HF. The AS patients without peripheral joint disease have higher LF, TP, variance, LF%, and HF than the patients with peripheral joint disease. The AS patients without uvetis have higher HF than the patients with uvetis. The total scores of BASDI, BASFI, and BAS-G do not show any association to HRV parameters. AS patients have significantly abnormal cardiac autonomic regulation. This is closely related with some inflammatory activities. Reduced autonomic function may be one of the factors of high cardiovascular risk in AS patients.